The impact of nanodrugs on the metagenome of tobacco rhizosphere soil - Lai, Chun-Mei; Xiao, Xiao-Shan; Liu, Li-Wei; Li, Xue-Li; Luo, Yu-Wei; Liang, Yan-Qi; Cheng, Yan; Qin, Yuan (Frontiers in Microbiology, 2026)
The occurrence of tobacco diseases seriously restricts the healthy development of the tobacco industry. Soil microorganisms play an important role in regulating ecosystem functions. However, the impact of nanodrugs on the rhizosphere microbial community of tobacco and its related functions is still unclear. Therefore, this study combined field experiments to evaluate the effect of nanodrugs in reducing diseases and combined metagenomic sequencing to further explore the micro-ecological mechanism of nanodrugs in stably reducing soil biological barriers. The results show that nanodrugs can significantly improve the health level of tobacco. Metagenomic sequencing found that nanodrugs treatment increased the diversity and abundance of bacterial communities and could regulate the structure of soil microbial communities. It could selectively recruit beneficial microorganisms such as Sphingomonas, Bradyrhizobium, Pseudomonas, and Nocardioides to assist tobacco in disease control. GO function analysis showed that nanodrug treatment groups had significant enrichment of energy metabolism-related functions such as electron transfer activity, ATPase activity, and redox processes. KEGG pathway analysis showed that the relative abundance of key metabolic pathways such as fatty acid metabolism, aminoacyl-tRNA biosynthesis, ribosome, and purine metabolism was significantly increased. This study found that nanodrugs may indirectly promote plant health and alleviate tobacco diseases by shaping microbial community structure, enriching beneficial bacterial communities, and activating key metabolic pathways. These findings provide a theoretical basis for the application of NMs in the regulation of agricultural micro-ecosystems.